PENTINGNYA PENDAFTARAN MEREK SUATU PRODUK - Anugraheni, Lilis Mardiana (Admisi dan Bisnis, 2014)
The brand is a sign of a picture, name, word, letters, figures, composition of colors, or the combination of these elements, which has distinguished features and uses in the trading of goods or services. Thus it can be said that the brand is the identity of a product or service. Furthermore, these products are known and trusted by the business community. It needs to be introduced, maintained the quality of the product and protected from the efforts from others who want to take an advantage of the brand of goods or services illegally. The product brand registration is a step to secure the ownership and legal protection. Besides from the field of law, the product brand registration also provides many other advantages which can be gained.